Fish Diversity in the Middle Part of Klawing River, Purbalingga Regency, Central Java Province - Saprudin Saprudin; Petrus Hary Tjahja Soedibja; Nuning Vita Hidayati; Rika Prihati Cahyaning Pertiwi; Isdy Sulistyo (Fakultas Perikanan dan Ilmu Kelautan, 2022)
Research on the diversity of fish species in the middle part of the Klawing River, Purbalingga Regency, Central Java Province, dealt with exploring the diversity of fish species in the middle part of the Klawing River. A survey method was applied to collect primary data during April-June 2022. Direct fish sampling was carried out at 3 stations in the middle part of Klawing River. The stations were chosen based on fish farming activities, domestic areas and accessibility. Station 1, 2, and 3 were located in Onje Village of Mrebet District, in Slinga and Lamongan Villages of Kaligondang District, respectively. The results showed that a total of 707 individuals were sampled, consisting of 23 species and 12 familia. Cyprinids dominated total samples. Diversity indexes were 1.94 and 1.99, in station 2 and 3, respectively. Diversity index in station 1 was 1.61. Dominance indexes were 0.26, 0.18, and 0.198, in station 1, 2, and 3, respectively. Evenness indexes consisted of 0.73 and 0.76, in station 1 and 2, respectively. However, evenness index in station 3 was 0.68.